Mortality and predictors among HIV-TB co-infected patients in Ethiopia: A systematic review and meta-analysis - Wubet Tazeb Wondie; Chalachew Adugna Wubneh; Bruck Tesfaye Legesse; Gebrehiwot Berie Mekonen; Alemu Birara Zemariam; Zenebe Abebe Gebreegziabher; Gezahagn Demsu Gedefaw; Gemechu Gelan Bekele; Belay Tafa Regassa (PLoS ONE, 2025)
Background HIV-TB co-infection poses a significant public health threat, notably in sub-Saharan Africa including Ethiopia. Despite this public health problem, studies in Ethiopia regarding the mortality of HIV-TB co-infection patients have been inconsistent, and the overall estimate of mortality was not determined. Accordingly, this meta-analysis aims to assess the magnitude of mortality and predictors among HIV-TB co-infected patients in Ethiopia. Methods A search of the literature was conducted from three databases (PubMed, Global Index Medicus, and CINHAL), and other sources (Google Scholar, Google, Worldwide Science). All observational studies that reported the mortality of HIV-TB co-infected patients in Ethiopia were included. Joanna Briggs Institute’s (JBI) quality appraisal checklist was used to assess the quality of studies. Effect sizes were pooled using the random effects model. Heterogeneity was assessed using Cochrane Q and I2 test statistics, and the prediction interval was determined. Subgroup analysis was conducted by region. To examine the presence of an influential study, a sensitivity analysis was done. Egger’s test was used to check publication bias. A non-parametric trim and fill analysis was carried out. Results A total of 886 studies were identified, using database searches and keywords. Of these, 37 met the criteria for inclusion. The pooled proportion of mortality among HIV-TB co-infected patients was found to be 18.42% (95% CI:14.27–22.57). In the subgroup analysis, the highest mortality was observed in the Tigray region at 31.86% (95% CI: 7.69–56.03), and the lowest mortality was reported in two general studies in Ethiopia 11.95 (95% CI: 4.19–19.00). From the examined 20 predictors, only four predictors such as Anaemia (HR = 2.25, 95% CI: 1.65–3.07), Poor adherence to ART (HR = 2.42, 95% CI: 1.39–4.21), not taking co-trimoxazole preventive therapy (HR = 1.87, 95% CI: 1.28–2.73), and extrapulmonary tuberculosis (HR = 1.23, 95% CI: 1.01–1.51) were significant predictors. Conclusions In Ethiopia, 18.42% of HIV-TB co-infected patients died. Anaemia, poor adherence, not taking CPT, and extrapulmonary tuberculosis were found to be significant predictors. Hence, the concerned stakeholders need to expand and strengthen the HIV-TB collaborative services and attention should be given to patients presented with the aforementioned predictors. Trial registration This meta-analysis has been registered in PROSPERO with registration number CRD42023466558.